Selkäydinvamman saaneiden henkilöiden kuntoutumispolkukokemukset : laadullinen ja narratiivinen tutkimus (FinSCI-tutkimus) - Tiitinen, Susanna (2024)
Spinal cord injury causes impairments of body function, participation and activities. Despite the impairments, a person with a spinal cord injury can live a fulfilling and meaningful life. Rehabilitation plays a significant role in assisting the person towards well-being. Rehabilitation is a process that improves the functionality and participation. This process is influenced by many personal factors, and therefore an individual rehabilitation pathway is created. Only few studies on the experiences of these individual rehabilitation pathways of persons with spinal cord injuries have been conducted. It is important to explore individual experiences of these rehabilitation pathways. This study explores the experiences of persons with spinal cord injury on rehabilitation pathways. The aim of the study was firstly, to produce knowledge about the rehabilitation pathways of persons with spinal cord injuries, and secondly, examine the differences and similarities between the experiences related to the rehabilitation process. The goal was to expand the understanding of the rehabilitation pathways of persons with spinal cord injuries as a qualitative and experiential phenomenon.